(untitled) - Dinh, The Nhan (Belgium, 2009)
The overall objectives of the present thesis were to develop improved technical protocols for prawn seed production through investigating a number of factors believed to play an import role in larval rearing success.
Keywords: Nuôi tôm,Shrimp culture,Macrobrachium rosenbergii